Becoming Useful. - Tillotson, Shirley (Canadian Historical Review, 2022)
Shirley Tillotson explores the origins and development of her attitudes towards university education and to the discipline of history. She concludes with a survey of some major historiographical developments since the 1980s and discusses how her work was influenced by those developments.